Innovation Approach to Efficiency Management in Catering Enterprises - I. N. Lukiyanchuk (Вестник Российского экономического университета имени Г. В. Плеханова)
Organization of catering for students, lecturers and employees is an important condition of university education activity and it is carried out by performing social and economic functions on the part of catering enterprises. Economic functions include production, sale and organization of consumption of products and services. They are quite close to social functions dealing with affordability of meals due to low prices, minimum amount of time for customer service and provision of healthy food. The work of catering enterprises aiming at these functions' performing focuses on technology of meals production and organization of customer service and ignores efficiency of functioning and calculation of relevant indicators. The article studies a new approach to managing efficiency of catering enterprises' work as structural divisions of universities. Insufficient understanding of the problem and absence of regulations in the field of catering enterprise management in university can cause high costs of their functioning, use of inefficient and out-dated organization of production and sale of meals and services. The author assesses the current problems of efficiency in catering enterprises' work in universities and substantiates the system of control indicators of enterprises' work, including receipts, a share of raw materials in the receipts, a share of remuneration in the receipts. The possibility to use controlling tools in managing efficiency of catering enterprises' work was grounded.